Water distribution at the electrified interface of deep eutectic solvents. Issue 8 (18th July 2019) - Mamme, Mesfin Haile; Moors, Samuel L. C.; Mernissi Cherigui, El Amine; Terryn, Herman; Deconinck, Johan; Ustarroz, Jon; De Proft, Frank
Abstract : Preferential asymmetric electrosorption of water onto a moderately polarized electrode surface. Abstract : Deep eutectic solvents (DESs) are a new class of solvents with wider potential window than that of water and high electrochemical stability, making them potential candidates for a wide range of electrochemical systems. However, due to the hygroscopic nature of DESs, the presence of latent water is unavoidable. Therefore, understanding the interfacial structure and the electrosorption and distribution of residual water at the electrified interface is of great importance for the use of these solvents in electrochemical systems. Using atomistic molecular dynamics, we explore the electrosorption and distribution of different amounts of water in 1 : 2 choline chloride–urea DES (Reline) at the electrified graphene interface. We found that both the water distribution and the interfacial structure are sensitive to the electrification of the graphene electrode. As a result, it is found that for moderately charged electrodes, water shows a preferential asymmetric adsorption in the vicinity of the positively charged electrode, partly due to strong intermolecular interactions with anions through hydrogen bonds. In contrast, for highly charged electrodes, water adsorbs at both electrodes due to a strongly enhanced external electrostatic interaction between the electrodes and the water dipoles.